2010
DOI: 10.1002/pbc.22808
|View full text |Cite
|
Sign up to set email alerts
|

Multi‐modal intervention for the inpatient management of sickle cell pain significantly decreases the rate of acute chest syndrome

Abstract: INTRODUCTIONSickle cell-related pain is the most common morbidity experienced by children and adults with sickle cell disease (SCD). Acute chest syndrome (ACS), though second to SCD-pain in frequency, contributes significantly to both morbidity and mortality in children with SCD. ACS is responsible for up to one-quarter of sickle cell-related mortality [1], and almost half of the deaths due to ACS are in children <20 years of age [2]. Furthermore, ACS during childhood negatively impacts long-term lung function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…Another strategy to prevent acute chest syndrome includes standardising hospital medical care and educating physicians and nursing staff to ensure patients receive optimum doses of opioids to relieve pain (but not cause sedation leading to atelectasis) and adequate intravenous and oral fluids. 19 When an inpatient multimodal strategy was implemented to manage vaso-occlusive pain, rates of acute chest syndrome decreased from 25% to 12% (p=0·003). 19 …”
Section: Acute Chest Syndrome In Sickle-cell Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Another strategy to prevent acute chest syndrome includes standardising hospital medical care and educating physicians and nursing staff to ensure patients receive optimum doses of opioids to relieve pain (but not cause sedation leading to atelectasis) and adequate intravenous and oral fluids. 19 When an inpatient multimodal strategy was implemented to manage vaso-occlusive pain, rates of acute chest syndrome decreased from 25% to 12% (p=0·003). 19 …”
Section: Acute Chest Syndrome In Sickle-cell Diseasementioning
confidence: 99%
“…19 When an inpatient multimodal strategy was implemented to manage vaso-occlusive pain, rates of acute chest syndrome decreased from 25% to 12% (p=0·003). 19 …”
Section: Acute Chest Syndrome In Sickle-cell Diseasementioning
confidence: 99%
“…These guidelines typically call for fluid resuscitation, pain control, antibiotics, bronchodilators, transfusion, and aggressive respiratory support. 5,6 Historically, SCD-associated ACS was considered a disease of early childhood. However, comprehensive care for infants and children with SCD has doubled survival to adulthood and increased the numbers of adolescents and young adults (A/YA) with SCDrelated complications such as ACS.…”
Section: (Continued On Last Page)mentioning
confidence: 99%
“…In the Cooperative Study of Sickle Cell Disease, a 29% incidence of ACS was reported in 3,751 subjects over a 2-year period, representing 12.8 episodes per 100 patient-years for HbSS disease (16). Before the recognition of PH, ACS was considered the leading cause of premature death, accounting for 25% of sickle cell-related mortality in early registry trials (8,(15)(16)(17). The associated mortality has decreased in the modern era of hydroxyurea therapy and early, more aggressive transfusion therapy (18).…”
Section: Acute Chest Syndromementioning
confidence: 99%
“…Therapies reported to prevent ACS in at-risk patients include preoperative blood transfusion (42), maintenance asthma therapy for children with asthma (43), maintenance hydroxyurea therapy (14,44), and the use of incentive spirometry during acute VOC hospitalizations (14,17,45).…”
Section: Acs Treatmentmentioning
confidence: 99%